Longitudinal aerodynamic characteristics of wau bulan wing-tail configuration with selected airfoil profile - Kusumohadi, Catur Setyawan (2011)
Wau bulan is one of the traditional Malaysia kites. Wau bulan consists of two parts which are wing and tail. Its configuration shows possible application as baseline planform of an aircraft. Wau bulan wing tail configuration is indicated as controllable and could meet the stability requirements. It is implied that wau bulan can be used as “Sensorcraft UAV configuration” that can meet the requirement of 360o unobstructed radar vision area. In this research, this wau bulan planform will be used as baseline of mini UAV configuration. Wau bulan wing planform shape that is close to elliptical shape, theoretically will have high efficiency factor. However, wau bulan has a low aspect ratio wing that causes high induced drag and will generate a low lift over drag ratio. Furthermore, wau bulan large tail area and short tail boom can also create significant trim drag. The focus of the research is to investigate the longitudinal aerodynamic characteristics of wau bulan wing tail configuration. It aims to verify that the wau bulan can fulfill the requirements of surveillance mini UAV. The research consists of baseline geometry definition, computational analysis and wind tunnel testing of isolated wau bulan wing and wing-tail configuration. Results of analysis would be compared with the assumed ones from initial sizing process. The baseline geometry was determined based on the initial sizing results, whereby initial sizing is the standard procedure of UAV initial calculation to predict the weight, power loading and wing loading based on surveillance mini UAV performance criteria. Airfoil was applied to create thickness of baseline geometry planform, where Kennedy Marsden Mod airfoil was chosen. It is a thick airfoil and was designed for low Reynolds number flow. FLUENT software was used as a tool for computational analysis, since it can accommodate 2D and 3D models. The results show the correlation of longitudinal aerodynamic characteristics between 2D airfoil with and without boundary layer mesh, isolated wing and wing tail configuration. The gaps between calculation results were justified by using the validation process. The boundary layer mesh shows significant effect toward aerodynamics calculation. Wind tunnel testing was conducted at UPM low speed open wind tunnel. This suction type wind tunnel is equipped with external balance to measure the aerodynamic forces and moments. Wind tunnel results show similar value of aerodynamics coefficient especially lift coefficient, between isolated wing and wing tail configuration. The effect of symmetrical tail cross section was observed at high angle of attack when the tail produces lift. Despite gaps between the experimental and computational results, the values still can be used to predict longitudinal aerodynamic characteristics of wau bulan wing tail configuration through validation process. The results show that the maximum lift coefficient of wing-tail configuration is close to the 2D airfoil one. Based on this condition, the improvement of wau bulan UAV can be predicted by using the 2D airfoil data. The analysis results prove that the longitudinal aerodynamic parameters of wau bulan UAV can be achieved. The maximum lift coefficient and lift over drag ratio values from computational and wind tunnel test are higher than the assumed ones during performance sizing. These results give opportunities to improve wau bulan UAV performance because the excess value could compensate additional weight or fuel.